Crustal melting, ductile flow, and deformation in mountain belts: Cause and effect relationships - Searle, M (2013)
Exhumed sections of migmatites are beautifully exposed in the middle crust of old orogens such as the Proterozoic Wet Mountains of Colorado and young Tertiary-active orogens such as the Himalaya and Karakoram. Migmatites and leucogranites occur both on a regional scale (e.g., Greater Himalayan Sequence) and along more restricted shear zones and strike-slip faults (e.g., Karakoram, Jiale, and Red River faults). Melting and deformation are clearly diachronous across orogenic belts over space and time, yet in general, deformation must precede regional metamorphism and melting in order to thicken the crust and increase pressure and temperature. Some deformation can be synchronous with partial melting and there is almost always post-melting deformation along shear zones or faults. The distinction between pre-, syn-, and post-kinematic granites in three dimensions, in pressure-temperature space, and in time becomes critical. In particular, mapping of macro- and micro-structures combined with precise U-Th-Pb dating of migmatitic leucosomes and granitic rocks in deformation zones can be used to constrain the relative timing of metamorphism, melting, ductile shearing and brittle faulting. In the Himalaya, multiple sill intrusions emanating from a regional migmatite terrane fed growth of leucogranite bodies over a time span of ~30 m.y. and channel flow, the southward extrusion of a partially melted section of the mid-crust, occurred along the Himalaya during the Miocene from ca. 24-15 Ma. The Karakoram batholith formed by pre- to post-collisional metamorphism, migmatisation and magmatism over a period lasting at least 65 m.y. Comparisons of the Himalaya and Karakoram migmatite-granite belts with the Proterozoic Wet Mountains in Colorado provide strong evidence for weak middle crust capable of aseismic flow, leading to question models of lithospheric rheology that call on strong middle crust. © 2013 Geological Society of America.